Ergonomic Evaluation of Computer Users by Rapid Office Strain Assessment (ROSA) Method and Its Relationship with the Prevalence of Musculoskeletal Disorders - Vida Rezaee-Hachesu; Rajabali Hokmabadi (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: In recent years, the rapid growth of technology and the use of computers have affected almost all workstations, and musculoskeletal disorders are very common among computer users. Therefore, this study aimed to evaluate the ergonomic status and prevalence of musculoskeletal disorders in computer users. Methods: This descriptive-analytical study was conducted on 100 Bank staff in Bojnurd, Iran. The Rapid Office Strain Assessment (ROSA) method and Nordic standard questionnaire were used to evaluate the ergonomic status, and determine the prevalence of musculoskeletal disorders, respectively. The data were analyzed in SPSS software (version22), through the Chi-square test, one-way ANOVA, and descriptive statistics. Results: The mean±SD age and work experience of users were determined at 34±6.9 and 15.1±0.7 years, respectively. A significant relationship was observed between gender and pain in the back (P=0.037), wrist/hand (P=0.032), knee (P=0.024), and upper back (P=0.054).The most common skeletal-muscular disorders in people were observed in the waist, neck, and upper back areas in the body, respectively. The mean±SD final ROSA score of the chair, phone-monitor, and mouse-keyboard was estimated at 3.7±1, 3.6±1.1, and 3.65±1.2, respectively, and the mean±SD of the final ROSA score was 4.4±0.9. Based on the ROSA method, 35 workstations had a risk score≥5, indicating the need for further evaluation and immediate corrections. Conclusion: According to the results of this study, it was found that work-environment factors that affect skeletal-muscular disorders include chair, mouse-keyboard, and phone-monitor, in the order of significance. Therefore, most of these injuries can be prevented by correcting the ergonomics of chairs and the proper placement of the mouse-keyboard.